22‐3: Tuning ETL Mobility by Disorder Passivation. Issue 1 (28th June 2021) - Kaiser, Simon; Symalla, Franz; Wehl, Daniel; Neumann, Tobias; Wenzel, Wolfgang
Abstract : In organic electronics (OE) application a high degree of control of material parameters such as transport levels and charge carrier mobilities is required to build a balanced device. We demonstrate that electron mobility of the prototypical electron transport material TPBi can be tuned freely by mixing it with a secondary electron transport inert material. We can in particular increase electron mobility in TPBi by up to a factor of 10 by diluting TPBi. This increase is due to a reduced electrostatic disorder in the mixed morphology. Using our predictive ab‐initio based modeling tools we can find the optimal mixture to maximize or pinpoint electron mobility in TPBi.